The Role of Character Based Islamic Education in Creating a Green School Environment - Gerry Mandala; Riska Okty Shakilla; Adi Shambono (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
Character-based Islamic education plays a crucial role in shaping environmental awareness and behavior in schools. This study aims to analyze the role of character-based Islamic education in shaping environmental behavior and supporting the realization of Green Schools. The research approach uses a literature review method with content analysis techniques. An analysis of 17 scientific literature, consisting of books and articles from national and international journals published between 2022 and 2025, focused on the integration of Islamic values into Islamic Religious Education (ISE), the process of character internalization, and ecological practices in the school environment. The results indicate that the values of trustworthiness, responsibility, simplicity, and the concept of khalifah fil The environment is the main foundation for fostering students' ecological awareness. The integration of religious beliefs, morals, and Islamic jurisprudence with environmental issues can transform religious values into concrete actions through habituation and exemplary behavior by educators. Changes in student behavior are reflected in habits of maintaining cleanliness, managing waste, and sustainably caring for the school environment. Character-based Islamic education also contributes to building an environmentally friendly school culture and strengthening synergy between schools and the community. This study confirms that character-based Islamic education is relevant as a moral and spiritual approach to addressing the challenges of the environmental crisis. The Green School model based on Islamic values has the potential to become a strategic alternative in developing sustainable education.